2017
DOI: 10.1103/physrevapplied.7.044020
|View full text |Cite
|
Sign up to set email alerts
|

Angle-Selective Reflective Filters for Exclusion of Background Thermal Emission

Abstract: Selective filtering of spectral and angular optical transmission has recently attracted a great deal of interest. While optical passband and stopband spectral filters are already widely used, angular selective transmission and reflection filtering represents a less than fully explored alternative. Nonetheless, this approach could be promising for several applications, including stray radiation minimization and background emission exclusion. In this work, a concept for angle-selective reflection filtering using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…For example, by patterning an array of antennas with a non-uniform scattering phase distribution on a SiC surface, free-space focusing of TE has been demonstrated [ Fig. 2(e)] 45 . Guided by a similar principle, a non-uniform metasurface composed of thermal emitters with varying angular emissivity patterns was shown to suppress TE into a certain area, forming a "dark spot" 51 . A recent theoretical study demonstrated TE from objects comprising an epsilon-near-zero material, enabled by the enhanced spatial coherence resulting from the stretching of the wavelength inside the epsilon-near-zero material 52 .…”
Section: Box 2-critical Couplingmentioning
confidence: 99%
“…For example, by patterning an array of antennas with a non-uniform scattering phase distribution on a SiC surface, free-space focusing of TE has been demonstrated [ Fig. 2(e)] 45 . Guided by a similar principle, a non-uniform metasurface composed of thermal emitters with varying angular emissivity patterns was shown to suppress TE into a certain area, forming a "dark spot" 51 . A recent theoretical study demonstrated TE from objects comprising an epsilon-near-zero material, enabled by the enhanced spatial coherence resulting from the stretching of the wavelength inside the epsilon-near-zero material 52 .…”
Section: Box 2-critical Couplingmentioning
confidence: 99%
“…7 is a filter-dependent property, caused by Bragg reflection at different incident angles. In contrast to emissivity plots in [26], Fig. 7 illustrates a complementary response, where the high-emissivity is restricted to a specific range of angles and frequency, with frequency selectivity mainly provided by the filter.…”
Section: Temperature Dependence Of Optical Constants and Emissivitymentioning
confidence: 99%
“…7 illustrates a complementary response, where the high-emissivity is restricted to a specific range of angles and frequency, with frequency selectivity mainly provided by the filter. However, in [26] a low-emissivity response is restricted to a specific range of angles and frequencies, with the frequency selectivity provided by material absorption. Table. 1 and applying (6), (7) and (8).…”
Section: Temperature Dependence Of Optical Constants and Emissivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal fields are inherently broadband and stochastic (8,9), making them challenging to manipulate via traditional optical techniques, which ultimately resort to interference phenomena. However, different photonic nanostructures have been successfully utilized to address this challenge, including corrugated surfaces supporting surface plasmons (1,9,10), photonic crystals (4,(11)(12)(13), resonators (14,15), metamaterials (16)(17)(18)(19), graphene (20), transformation optics (21), and angle-selective filters (22,23). In essence, these methodologies utilize structural degrees of freedom to either suppress (e.g., photonic bandgaps, angle-selective filters) or enhance (e.g., resonant cavities, corrugated surfaces) specific modes, thus leading to an enhanced spatial coherence that allows for a partial control of thermal fields.…”
mentioning
confidence: 99%